Pramuka Sebagai Wadah Meningkatkan Nilai Karakter Peduli Sosial - Rahmawati, Laili Ni'matul; Yunus, Siti Maryam (Institut Agama Islam Negeri Ponorogo, 2020)
ABSTRACTThis study aims to determine whether there is an effect of scouting education activities on increasing the value of the social care character of students at MTs Plus Al-Hadi. In this study, researchers used a regression quantitative approach. The population in this study amounted to 71 students. The data analysis technique used statistical formulas, namely simple linear regression and multiple regression. The sampling technique in this study using saturated sampling technique. The data collection technique uses a questionnaire. From the results of this study, the following conclusions can be drawn: 1) based on the results of the tcount of 2.782 and ttable of 1.66724, (tcount> ttable) the coaching pattern variable has an influence on increasing the value of social care character in MTs Plus Al-Hadi; 2) Based on the results of tcount of 5.386 and ttable of 1.66724, (tcount> ttable) the activeness of participating in scouts has an effect on increasing the value of social care character in MTs Plus Al-Hadi; 3) Fcount: 16.535 and Ftable 3.13; means Fcount> Ftable at a 5% error rate, the significance level is 0.000 <0.05 (= 5%), then scouting activities have an influence on increasing the value of social care characters in MTs Plus Al-Hadi.ABSTRAKPenelitian ini bertujuan untuk mengetahui apakah terdapat pengaruh kegiatan pendidikan kepramukaan terhadap peningkatan nilai karakter peduli sosial siswa MTs Plus Al-Hadi. Dalam penelitian ini peneliti menggunakan pendekatan kuantitatif regresi. Populasi dalam penelitian ini berjumlah 71 siswa. Teknik analisis data menggunakan rumus statistik yaitu regresi linier sederhana dan regresi berganda. Teknik pengambilan sampel dalam penelitian ini menggunakan teknik sampling jenuh. Teknik pengumpulan data menggunakan kuesioner. Dari hasil penelitian ini dapat ditarik kesimpulan sebagai berikut: 1) Berdasarkan hasil thitung 2,782 dan ttabel 1,66724, (thitung> ttabel) variabel pola pembinaan berpengaruh terhadap peningkatan nilai karakter peduli sosial. di MTs Plus Al-Hadi; 2) Berdasarkan hasil thitung sebesar 5,386 dan t tabel sebesar 1,66724 (thitung> ttabel) keaktifan mengikuti pramuka berpengaruh terhadap peningkatan nilai karakter peduli sosial di MTs Plus Al-Hadi; 3) Fhitung: 16.535 dan Ftabel 3.13; Berarti Fhitung> Ftabel pada taraf kesalahan 5%, taraf signifikansi 0,000 <0,05 (= 5%), maka kegiatan pramuka berpengaruh terhadap peningkatan nilai karakter peduli sosial di MTs Plus Al-Hadi.